Impact of PD ‐1 Inhibitor Timing Relative to Locoregional Therapy on Outcomes in uHCC Treated With Lenvatinib‐Based Triple Therapy - Jian He; Jian Chen; Bohua Yu; Fuqun Wei; Weifu Liu; Peishu Huang; Songhui Wu; Xiang You; Zhisheng Chen; Ziqi Lin; Wuhua Guo; Shaowu Zhuang; et al. (Liver International, 2026)
ABSTRACT Background and Aims The optimal sequencing of programmed cell death protein 1 (PD‐1) inhibitors relative to locoregional therapy (LRT) in unresectable hepatocellular carcinoma (uHCC) remains undefined. This study evaluated the impact of PD‐1 inhibitor timing on outcomes in patients receiving hepatic arterial infusion chemotherapy (HAIC) or transarterial chemoembolisation (TACE) plus lenvatinib and PD‐1 inhibitors. Methods Patients with initially uHCC who received LRT in combination with lenvatinib and PD‐1 inhibitors across six academic centres were stratified by LRT modality (HAIC vs. TACE) and categorised into two groups based on PD‐1 inhibitor timing (Pre‐LRT PD‐1 and Post‐LRT PD‐1 group). Overall survival (OS) and progression‐free survival (PFS) were estimated using the Kaplan–Meier method; propensity score matching (PSM) and landmark analyses were applied to mitigate potential biases. Results A total of 350 patients were included, with 185 in the HAIC cohort and 165 in the TACE cohort. Pre‐LRT PD‐1 group was associated with significantly improved OS in the overall population, driven primarily by the HAIC cohort rather than the TACE cohort (34.03 m vs. 30.6 m, p = 0.032); these findings remained consistent after PSM and landmark analyses. Subgroup analyses further supported the survival benefit of Pre‐LRT PD‐1 initiation. After PSM, Pre‐LRT PD‐1 was also associated with significantly prolonged PFS in the HAIC cohort. According to RECIST 1.1 criteria, the Pre‐LRT PD‐1 group showed a higher objective response rate (ORR) ( p = 0.002). Conclusions In patients with uHCC receiving HAIC combined with lenvatinib and PD‐1 inhibitors, initiation of PD‐1 inhibitors prior to HAIC is associated with superior survival outcomes.